Epilithic and epiphytic diatoms of Golbasi Lake, Turkey - Yildirim, V; Cetin, AK (Oikos Publ Inc, 2006)
We surveyed the epilithic and epiphytic diatoms in Golbasi Lake. Seventy-two species were recorded, most of which were both epiphytic and epilithic. Species richness of these diatoms was higher in spring and early summer than in autumn and winter.